CONSUMER PREFERENCES: PRICE AND SERVICE QUALITY: AIRLINE INDUSTRY - Yajid, Mohd Shukri Ab; shukri, Sakinah mohd; Tham, Jacquline (International Journal of Psychosocial Rehabilitation, 2020)
Consumers have different types of preferences, which are directly affected by price and service quality. In this research study, it is discovered on how consumer preferences in the airline industry can be affected by the two variables mentioned and how they can contribute to the levels of consumer satisfaction. Focus has been given to consumers who have experienced MAS and/or Air Asia airlines. Hence, comparison can be made based on the consumers’ reaction towards the price and service quality of both Malaysia Airlines System (MAS), and AirAsia. These tools include descriptive analysis, one independent t-test and Chi Square test. In conclusion, after working on this research, the results show that there is significant relationship between price and service quality in the airline industry that contributes in influencing consumer decision making.